2022
DOI: 10.3390/ani12010110
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Characteristics of Yogurt from Sheep Fed with Moringa oleifera Leaf Extracts

Abstract: This study determined the effect of feeding Moringa oleifera (MO) leaf extracts to lactating ewes on the physicochemical composition of their milk and yogurt during storage (4 °C for 14 days) and the sensory acceptance of the yogurt. Over 45 days, 24 multiparous lactating Pelibuey and Katahdin ewes (two days in lactation) were randomly assigned to four groups: MO-0, basal diet (BD) + 0 mL MO; MO-20, BD + 20 mL MO; MO-40, BD + 40 mL MO; and MO-60, BD + 60 mL MO. In the milk, an increase of 6% in protein, 26% in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Post-fermentation acidification in yogurt is also due to the metabolic activity of the starter cultures during the cold storage period of the product (Sccaro et al, 2009;Rezaei et al, 2023a). A drop in pH during 14 days of storage was also observed in the study of Mendoza-Taco et al (2022) for sheep yogurt enriched with Moringa oleifera leaf extract. Previous studies have stated that the increased trend in acidity is due to the activity of lactic acid bacteria and the production of lactic acid and other organic acids (Rezaei et al, 2023a).…”
Section: Results and Discussion Ph And Acidity Determinationmentioning
confidence: 91%
“…Post-fermentation acidification in yogurt is also due to the metabolic activity of the starter cultures during the cold storage period of the product (Sccaro et al, 2009;Rezaei et al, 2023a). A drop in pH during 14 days of storage was also observed in the study of Mendoza-Taco et al (2022) for sheep yogurt enriched with Moringa oleifera leaf extract. Previous studies have stated that the increased trend in acidity is due to the activity of lactic acid bacteria and the production of lactic acid and other organic acids (Rezaei et al, 2023a).…”
Section: Results and Discussion Ph And Acidity Determinationmentioning
confidence: 91%
“…At the same time, the texture and flavor were not affected by the addition of ginseng. With the addition of moringa to yogurt, the results of the study mentioned by Mendoza-Taco et al [ 66 ] showed that the yogurt samples were not affected in relation to the sensory traits assessed. Meanwhile, in a study [ 67 ] attempting to enhance the vitality-boosting fermented camel milk drink with sugary date fibers and demonstrate its effects on sensory traits, the results indicated that adding 12.5% of sugary dates fiber was preferred by sensory traits assessors.…”
Section: Resultsmentioning
confidence: 99%
“…Effects of M. oleifera essential oils (0.3 and 0.6 ml/day) supplementation on milk quality and fatty acid profile in dairy sheep were investigated by Selmi et al (2020) and revealed increased milk fat, unchanged protein, decease urea nitrogen, decreased saturated, and decreased unsaturated fatty acid profiles. Mendoza-Taco et al (2022) investigated the impacts of M. oleifera leaf extracts (20 ml) on the physicochemical characteristics of yogurt prepared from sheep milk. M. oleifera leaf extracts positively affected the physical and chemical composition of milk and yogurt during storage.…”
Section: Milk Production and Compositionmentioning
confidence: 99%
“…M. oleifera leaves are known to contain calcium (4X) and protein (2X) compared to milk, vitamin C (7X) compared to oranges, potassium and iron (3X) compared to banana and spinach respectively, and vitamin A (4X) compared to carrots (Thurber and Fahey, 2009;Razis et al, 2014). The leaves of M. oleifera contain beta-carotene and other phytochemicals known for their antioxidant ability (rutin, quercetin, kaempferol, and caffeoylquinic acids); antioxidant vitamins (A, C, and E) and antioxidant micronutrients (zinc and selenium), which play important roles in fertility performance ( Jaiswal et al, 2009;Vongsak et al, 2014;Afzal et al, 2020) as well as contributing to an improvement in growth performance (Warastomo et al, 2021;Pandey et al, 2022), blood metabolites (Akanmu et al, 2020;EL-Hedainy et al, 2020), and milk production and composition (Kholif et al, 2016(Kholif et al, , 2019Mendoza-Taco et al, 2022). Due to the several aforementioned nutritional benefits of M. oleifera, this review is compiled and discussed such effects on mammals (Figure 1).…”
Section: Introductionmentioning
confidence: 99%